Evaluation of an Immunomodulatory Probiotic Intervention for Veterans With Co-occurring Mild Traumatic Brain Injury and Posttraumatic Stress Disorder: A Pilot Study - Brenner, Lisa A.; Forster, Jeri E.; Stearns-Yoder, Kelly A.; Stamper, Christopher E.; Hoisington, Andrew J.; Brostow, Diana P.; Mealer, Meredith; Wortzel, Hal S.; Postolache, Teodor T.; Lowry, Christopher A. (Frontiers in Neurology, 2020)
Abstract Background: United States (US) military Veterans returned from Operation Enduring Freedom/Operation Iraqi Freedom/Operation New Dawn (OEF/OIF/OND) with symptoms associated with mild traumatic brain injury (mTBI; i.e., persistent post concussive [PPC] symptoms) and posttraumatic stress disorder (PTSD). Interventions aimed at addressing symptoms associated with both physical and psychological stressors (e.g., PPC and PTSD symptoms) are needed. This study was conducted to assess the feasibility, acceptability, and safety of a probiotic intervention, as well as to begin the process of evaluating potential biological outcomes. Methods: Pilot randomized controlled trial with US military Veterans from recent conflicts in Iraq and Afghanistan. Those enrolled had clinically significant PPC and PTSD symptoms. Participants were randomized to intervention (Lactobacillus reuteri [L. reuteri] DSM 17938) or placebo supplementation at a 1:1 ratio, stratified irritable bowel syndrome status. Thirty-one Veterans were enrolled and randomized (15 to the control condition, and 16 to the probiotic condition). Results: Thresholds for feasibility, acceptability, and safety were met. Probiotic supplementation resulted in a decrease in plasma C-reactive protein (CRP) concentrations that approached statistical significance (p = 0.056). Although during the Trier Social Stress Task (TSST; administered post-supplementation) no between-group differences were found on a subjective measure of stress responsivity (Visual Analogue Scale), there was a significantly larger increase in mean heart beats per minute between Baseline and the Math task for the control group as compared to the probiotic group (Estimated Change, Probiotic 5.3 [-0.55, 11.0], Control 16.9 [11.0, 22.7], p = 0.006). Conclusions: Findings from this trial support the feasibility, acceptability, and safety of supplementation with an anti-inflammatory/immunoregulatory probiotic, L. reuteri DSM 17938, among Veterans with PPC and PTSD symptoms. Moreover, results suggest that CRP may be a viable inflammatory marker of interest. A larger randomized controlled trial aimed at measuring both biological and clinical outcomes is indicated.